Sistem Pendeteksi Hama Wereng pada Tanaman Padi Menggunakan Sensor ADXL335 Berbasis Gelombang Radio dan Light Trap - Junita Insyirah N. H.; Ayu Kirani Azzahra; Menik Ariani; Erry Koriyanti; Ari Hayati; Khairul Saleh; Assaidah Adnan (Universitas Andalas, 2026)
One of the strategies issues that determines the success of a rice crop is how to eradicate pests without using chemicals. Conventional pest control generally uses pesticides that can cause pest resistance, increase production costs, and risk environmental pollution. This study proposes an early detection system for planthopper pests based on the ADXL335 accelerometer sensor to detect vibrations or abnormal movements in rice stalks. Vibration data detected by the ADXL335 is processed together with wind speed data from the Anemometer Sensor to distinguish between vibrations caused by pests and vibrations from wind gusts. If a pest anomaly is detected, the system will automatically activate a Light Trap to physically capture the pests. Furthermore, real-time notifications are also sent to farmers via radio waves via the Telegram short message service. This system is expected to reduce dependence on pesticides, save costs, and support the government's agenda of modernizing agriculture to maintain national food security.